1999
DOI: 10.1016/s0034-5687(99)00024-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen sensing and signaling: impact on the regulation of physiologically important genes

Abstract: A growing number of physiologically relevant genes are regulated in response to changes in intracellular oxygen tension. It is likely that cells from a wide variety of tissues share a common mechanism of oxygen sensing and signal transduction leading to the activation of the transcription factor hypoxia-inducible factor 1 (HIF-1). Besides hypoxia, transition metals (Co 2+ , Ni 2+ and Mn 2+ ) and iron chelation also promote activation of HIF-1. Induction of HIF-1 by hypoxia is blocked by the heme ligands carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(105 citation statements)
references
References 63 publications
(64 reference statements)
3
101
0
1
Order By: Relevance
“…A cytosolic flavoheme protein acts as an oxygen sensor that detects decreased oxygen tension and activates transcription factors through signal transduction pathways. 153,154 Hypoxia inducible factor 1 (HIF-1) is a major transcription factor. 155 The activation of HIF-1 depends upon signaling-dependent rescue of its alphasubunit from oxygen-dependent degradation in the proteasome and formation of a heterodimer with HIF1beta, which then translocates to the nucleus and impacts on the transcription of genes that are upregulated by hypoxia [156][157][158] Activation of HIF-1 has been shown to increase production of a variety of factors implicated in the pathogenesis of diabetic retinopathy (eg ischaemic retina 159 ).…”
Section: Leukocyte Activation and Adherencementioning
confidence: 99%
“…A cytosolic flavoheme protein acts as an oxygen sensor that detects decreased oxygen tension and activates transcription factors through signal transduction pathways. 153,154 Hypoxia inducible factor 1 (HIF-1) is a major transcription factor. 155 The activation of HIF-1 depends upon signaling-dependent rescue of its alphasubunit from oxygen-dependent degradation in the proteasome and formation of a heterodimer with HIF1beta, which then translocates to the nucleus and impacts on the transcription of genes that are upregulated by hypoxia [156][157][158] Activation of HIF-1 has been shown to increase production of a variety of factors implicated in the pathogenesis of diabetic retinopathy (eg ischaemic retina 159 ).…”
Section: Leukocyte Activation and Adherencementioning
confidence: 99%
“…In hypoxic conditions (1% O 2 , 1-6 h), the mRNA level of HIF-1a, Egr-1 and MTF-1 increased significantly in HeLa and C2C12 cells (Table 2), which is consistent with the data published by others. 8,10,18 We next tested whether the increased expression of each transcription factor translates into increased binding to its target DNA motif. Gel shift assays with the nuclear extracts prepared in both normoxic and hypoxic conditions …”
Section: Validation In Different Cells and With Other Cdnasmentioning
confidence: 99%
“…17 These hypoxia mimetics are thought to exploit the cellular oxygensensing mechanism and the hypoxic signal-transduction pathway that lead to stimulation of several hypoxiaresponsive genes. 18 In the present study, we hypothesized that combinations of the HRE, MRE and Egr-1-binding site (EBS) might provide novel means by which to enhance the level of hypoxic induction and to control target gene expression with hypoxia mimetics. Once successful, such chimeric enhancer vectors could rigorously restrict therapeutic gene expression to hypoxia-or hypoxia mimetics-enriched tissues, thereby providing greatly enhanced condition-specific expression.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Specific hypoxia-responsive elements (HRE) have been cloned and employed for expression of therapeutic transgenes in hypoxic tumor cells. 4,9,18 Using HRE from the mouse phosphoglycerate kinase 1 gene (pgk1) to drive expression of cytosine deaminase (CD), Dachs et al 4 demonstrated that CD was induced 6.8-fold under hypoxic conditions and caused tumor cell killing when the prodrug 5-fluocytosine (5-FC) was administered.…”
Section: Units (Rlu)/mg Protein) Control Nt2 Cells Transfected With mentioning
confidence: 99%